(untitled) (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2021)
The purpose of this study was to determine the effect of understanding tax law, taxation system, taxation, and economic motives on tax evasion (a case study of taxpayers in Kulon Progo Regency). This research method is determined by causality method and primary data using a questionnaire. This study took a sample of taxpayers in Kulon Progo Regency. This data collection technique uses a questionnaire questionnaire. The analytical method used is multiple regression analysis which is processed using IBM SPSS version 20. The number of data processed is 100 respondents. Based on the results of the analysis of the understanding of tax law, the tax system, and taxes have a negative effect on tax evasion. The results of this study also conclude that economic motives have a positive effect on tax evasion